Immunomodulatory activities of curcumin-stabilized silver nanoparticles: Efficacy as an antiretroviral therapeutic. (17th November 2017) - Sharma, Rakesh Kumar; Cwiklinski, Katherine; Aalinkeel, Ravikumar; Reynolds, Jessica L; Sykes, Donald E.; Quaye, Elizabeth; Oh, James; Mahajan, Supriya D.; Schwartz, Stanley A.
ABSTRACT: We synthesized and characterized curcumin-stabilized silver nanoparticles (Cur-AgNP) and found them to be 45 nm by dynamic light scattering with a maximum absorbance at 406 nm. We evaluated Cur-AgNP for immunomodulatory activities and their potential as an antiretroviral agent. The antiretroviral effects of Cur-AgNP were determined in ACH-2 cells latently infected with human immunodeficiency virus (HIV)-1. ACH-2 cells, 200, 000/ml, were treated with Cur-AgNP for 24–48 h. Expression of HIV-1 LTR and p24, the pro-inflammatory cytokines, IL-1β, TNF-α, and NF-κB was quantitated. Treatment of ACH-2 cells latently infected with HIV-1 with Cur-AgNP produced no toxic effects but significantly inhibited the expression of HIV-1 LTR (−73%, P < 0.01) and p24 (−57%, P < 0.05), IL-1βα (−61%, P < 0.01), TNF-αα (−54%, P < 0.05), IL-6 (−68%, P < 0.01), and NF-κB (−79%, P < 0.0001) as compared to untreated controls. Thus, Cur-AgNP have therapeutic potential as direct antiretroviral agents, as well as having immunomodulatory activities inhibiting the expression of pro-inflammatory mediators induced by infection with HIV-1. Experimental controls, such as curcumin alone, and conventional silver nanoparticles capped with citric acid, produced no similar biological effects. We conclude that treatment of HIV-1 infected cells with Cur-AgNP significantly reduced replication of HIV by inhibition of NF-κB nuclear translocation and the downstream expression of the pro-inflammatory cytokines IL-1β, TNF-α, and IL-6. Subsequent in vivo studies with Cur-AgNP using a humanized mouse model of HIV infection are underway.